Gama Tirtha Ideology in Ancient Myth of Ratu Gede Tengahing Sagara (e-Journal of Linguistics, 2020)
The Balinese can not be separated from their ancestral beliefs.The ancestral or idiological beliefs in Balinese society areconveyed through myths. One of the most well-known myths inBali is the Ratu Gede myth. The myth of Ratu Gede is verytrusted and believed in constructing worship rituals. Theworship ritual that is routinely performed is the NanglukMarana ritual. Nangluk Marana is a ritual handed down by themyth of Ratu Gede Nusa Penida. The myth of Ratu Gede is notlimited to the figure of Ratu Gede Nusa Penida, but in Bali italso found a similar myth called the myth of Ratu GedeTengahing Sagara. The name sagara which means the sea hasshown its identity as the ruler of the ocean. The myth of RatuGede Tengahing Sagara as the ruler of the ocean is not onlybeing told on the coast, but also spread out to the highlands. Theidiological influence of Ratu Gede Tengahing Sagara's myth tothe highlands cannot be separated from the intertwining ofstories handed down from generation to generation. Theintertwining that can be seen in the form of Ratu GedeTengahing Sagara's sacred route is always related to watercivilization.
Keywords: Ratu Gede Tengahing Sagara; aquatic civilization; idiological meaning